2020
DOI: 10.1149/1945-7111/ab9cc9
|View full text |Cite
|
Sign up to set email alerts
|

TCNQ Confined in Porous Organic Structure as Cathode for Aqueous Zinc Battery

Abstract: The rechargeable Zn 2+ ion batteries are promising for the sustainable energy storage device applications. Recently they have been extensively evaluated for finding new cathode material and prevention of dendrite growth at Zn plate anode. Herein we have evaluated redox active organic molecule 7,7,8,8Tetracyanoquino dimethane (TCNQ) as a cathode material for aqueous zinc battery with zinc plates as anode in 1 M ZnSO 4 . The charging/discharging of the battery was associated with formation and deformation of Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The introduction of multifunctional CCP additive effectively improved the electrochemical performance, leading to a boosted capacity of up to 171 mAh g −1 with longer cycling stability versus pure TCNQ cathode. [ 97 ] Grzybowski et al reported a systematic work of 2D COF‐protected zinc anodes using a series of 1,3,5‐triphloroglucinol (TFP)‐based COFs (labeled as a DIP series). The authors designed a dip‐coating method to fabricate large self‐assembling COF films (30 × 12 cm 2 ) on zinc and other substrates (Figure 9c) with a controllable thickness varying from 5 to over 100 nm.…”
Section: D Carbon‐rich Polymersmentioning
confidence: 99%
“…The introduction of multifunctional CCP additive effectively improved the electrochemical performance, leading to a boosted capacity of up to 171 mAh g −1 with longer cycling stability versus pure TCNQ cathode. [ 97 ] Grzybowski et al reported a systematic work of 2D COF‐protected zinc anodes using a series of 1,3,5‐triphloroglucinol (TFP)‐based COFs (labeled as a DIP series). The authors designed a dip‐coating method to fabricate large self‐assembling COF films (30 × 12 cm 2 ) on zinc and other substrates (Figure 9c) with a controllable thickness varying from 5 to over 100 nm.…”
Section: D Carbon‐rich Polymersmentioning
confidence: 99%
“…Figure S9 shows that at pristine state (Supporting Information: Figure S9a,d), XPS peak for -C≡N is the main functional group, while at 0.5 V (Supporting Information: Figure S9b two new diffraction peaks are generated near 2θ = 9.2°and 21.8°and the peak intensity continuously enhances along discharging, indicating that a new substance is formed, which is preliminarily determined to be Zn-TCNQ. 20 When charging is completed, the diffraction peaks are recovered to that of the initial state, indicating a highly reversible process of p-TCNQ during charging/discharging.…”
Section: Av = Bmentioning
confidence: 94%
“…When discharged to 0.77 V, rod morphology is observed on the surface of the electrode; when fully discharged to 0.5 V, more rods appeared, exhibiting the formation of Zn-TCNQ, since it was reported to be onedimensional rods. 20 When charged to 1.16 V, the TCNQ particles gradually recover. At a fully charged state (1.35 V vs. Zn 2+ /Zn), the TCNQ electrode returns to its original morphology, which also illustrates the reversibility of TCNQ along charging and discharging.…”
Section: Av = Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The high carrier mobility in Zn(TCNQ) 2 could induce low interfacial impedance and high current-carrying capacity, resulting in uniform surface current distributions of Zn anode. 30 Furthermore, the oxidation potential of Zn(TCNQ) 2 can be confirmed to be 1.125 V (vs Zn/Zn 2+ ), 23 suggesting that Zn(TCNQ) 2 will not undergo redox reactions during the Zn plating/stripping process. Importantly, the cyano groups (−CN) in Zn(TCNQ) 2 can capture and immobilize the highly active H 2 O molecules from [Zn(H 2 O) 6 ] 2+ via hydrogen bonding, which could accelerate the desolvation process of Zn 2+ .…”
Section: Metrics and Morementioning
confidence: 99%